Analisis Kebutuhan Keluarga Berencana yang Tidak Terpenuhi (Unmet Need) pada Wanita Usia Subur - Lanova Dwi Arde M.; Sri Novita Lubis; Puteri Citra Cinta Asyura Nasution (Jurnal Kesehatan, 2021)
The high number of unmet needs affects the Total Fertility Rate (TFR) and birth spacing as well as the occurrence of unwanted pregnancies which also increases the risk of death in the mother. This study aims to analyze the unmet need for family planning in women of childbearing age in West Medan. This research is a quantitative study using a cross-sectional study design. The research sample was women of childbearing age in Karang Berombak Village, West Medan, Medan City. Samples were taken in 7 neighborhoods with a simple random method. Data obtained a sample of 162 people. The research data were analyzed using statistical software with logistic regression methods. The results showed that the number of unmet needs in Karang Berombak Village was 24.7%. Factors related to the incidence of unmet need, the decision to have KB is a decision by yourself / not involving the husband (Exp (B) 1.58 with a p-value of 0.02, after being controlled with the knowledge variable. The conclusion is that the number of unmet needs in Karang Village Wavy West Medan is still higher than the North Sumatra and the national rate. The factors that are associated with the incidence of unmet need are low levels of knowledge and the decision for family planning was the only women’s decision/not involving the husband. It is recommended to related agencies be more active in socializing about family planning and its side effects so that there is no misunderstanding about family planning.